PEMANFAATAN POTENSI ANGIN LAUT PENGGERAK MESIN PERAHU NELAYAN PENGGANTI MESIN BERTENAGA MINYAK - Budi Prijo Sembodo; Rony Haendra Fora; Sri Widyastuti (WAKTU, 2014)
Wind Power Plants convert wind energy into electrical energy using wind turbines orwindmills. The problem is when in season Mitra wind / west season , fishermen catching crabs cannot directly capture crabs . The process can wait for days , until the right time to spread the net.When should wait for the weather improves fuel becomes a major problem . Fishermen do nothave the ability to purchase fuel in bulk .Results KKN PPM Theme : minimation fuel problem ,known as fossil fuels , the use of the traditional mindset change boat engine oil into the enginefueled with energy saving environmentally friendly energy alternatives that are cheaper , achievededucation for sustainable development , economic improvement occurred residents by selling theproducts of wind energy boat engine. Method in empowerment , operational steps to correct theproblem, the volume of work in the form of JKEM and the total volume of work